Evaluating with the Success Case Method - Gram, Tom (2011)
The method was developed by Robert Brinkerhoff as an alternative (or s upplement) to the Kirkpatrick approach and its derivatives. It is very simple and fast (which is part of it’s appeal) and goes something lik e this: Step 1. Identify targeted business goals and impact expectatio ns Step 2. Survey a large representative sample of all participants in a program to identify high impact and low impact cases Step 3. Analyz e the survey data to identify: a small group of successful participant s a small group unsuccessful participants Step 4. Conduct in-depth int erviews with the two selected groups to: document the nature and busin ess value of their application of learning identify the performance fa ctors that supported learning application and obstacles that prevented it. Step 5. Document and disseminate the story report impact applaud successes use data to educate managers and organization The process pr oduces two key outputs In-depth stories of documented business effect that can be disseminated to a variety of audiences Knowledge of factor s that enhance or impede the effect of training on business results. F actors that are associated with successful application of new skills a re compared and contrasted with those that impede training. It answers practical and common questions we have about training and other initi atives: What is really happening? Who’s using what, and how well? Who’ s not using things as planned? What’s getting used, and what isn’t? Wh ich people and how many are having success? Which people and how many are not? What results are being achieved? What value, if any, is being realized? What goals are being met? What goals are not? Is the interv ention delivering the promised and hoped for results? What unintended results are happening? What is the value of the results? What sort of dollar or other value can be placed on the results? Does the program a ppear to be worthwhile? Is it producing results worth more than its co sts? What is its return on investment? How much more value could it pr oduce if it were working better? How can it be improved? What’s helpin g? What’s getting in the way? What could be done to get more people to use it? How can everyone be more like those few who are most successf ul?